New forms of learning for vocational education : mobile learning - social learning - game-based learning - Witt, Claudia de [Verfasser] (My University, 2013)
"The Internet has become a staple element of information and communication infrastructures throughout society and culture, including the workplace. Low-cost, high-performance mobile devices coupled with the universal Internet accessibility and simple applications (apps) have brought about marked changes in our information and communication habits. In response to these changes, new forms of learning have emerged in step with these developing technologies. This article introduces several of these new forms of learning - mobile learning, social learning and game-based learning - and reflects on their potential for vocational learning." (Autorenreferat, BIBB-Doku)
Keywords: L 4.1.2 Elektronische Medien; Digitale Medien; Berufsbildung; E-Learning; Mobiles Lernen; Soziales Lernen